Creep measurement and choice of creep laws for BGA assemblies' reliability simulation. (September 2018) - Pin, S.; Guédon-Gracia, A.; Delétage, J.-Y.; Frémont, H.
Abstract: Since the replacement of hazardous materials by the RoHS directive, the intensive use of lead free solder materials generates countless studies to find new acceleration factors. In that scope, identifying the failure mechanisms involved in accelerated thermal tests has become of great concern for reliability design. Numerical tools are commonly developed for predictive analysis but their accuracy and capacity to be transposed to multiple technologies rely in part on the right choice of material behaviour. This study proposes to fit material coefficients of 4 different available creep laws to a same set of experiments. A unique couple of Finite Element models is defined using global/local calculations. Global calculation gives the assembly behaviour under thermal loads that is used to feed a part of the assembly with a more refined mesh to calculate locally a BGA ball that behaves following the Garofalo's, Anand's, Darveaux's laws of creep. The discrepancies that this comparison highlights, show how much care needs to be taken at that step of modeling for reliability prediction.